Membangun Kesadaran Ekoteologi dan Refleksi Kebijakan Tatakelola SDA - Muhammad Aras Prabowo; Siti Nur Hanifa; Aloys Budi Purnomo; Farid F. Saenong; Nur Arfiyah Febriani; Habsyah Fitri Aryani; Handy Fernandy; Adrinoviarini Adrinoviarini; Asiroch Yulia Agustina; Ahsanul Minan (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2026)
Repeated flooding on the island of Sumatra over the last decade has shown that hydrometeorological disasters cannot be understood merely as weather-related problems, but rather as a nexus of ecological crisis, Natural Resource (NR) governance, and exploitative patterns of human–nature relations. This community service activity was conducted in the environment of Istiqlal Mosque PKUMI through panel discussions, public dialogues, and the formulation of policy recommendations. The ecotheology framework was employed to connect spiritual dimensions, public ethics, and environmental policy; meanwhile, “ecological repentance” was used as a transformative concept: changes in awareness, behavioral transformation, and policy correction. The results of the activity indicate four main findings: (1) ecotheology is effective as a “moral language” to broaden acceptance of pro-environmental policies; (2) criticism of the technocratic-extractive paradigm needs to be integrated with the principles of precaution and ecological justice; (3) ecotheological education through a love-based/eco-empathy curriculum has the potential to build intergenerational ecological ethics; and (4) policy recommendations emphasize a moratorium on problematic permits, meaningful public participation (FPIC), enforcement of the polluter pays principle, and the reallocation of extractive subsidies for basic services and ecological restoration. The main outputs of this community service activity are policy recommendations and the strengthening of collaborative networks across faith communities, universities, Islamic boarding schools, mass organizations, and policymakers as the foundation of an ecological repentance movement.